RELATIONSHIP BETWEEN PRINCIPAL ROLE, WORK MOTIVATION AND JOB SATISFACTION WITH ELEMENTARY SCHOOL TEACHER PERFORMANCE - Irawati, Agustina; Aslamiah, Aslamiah; Saleh, Muhammad (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
This study aims to: (1) Describe the role of the principal, teacher work motivation, teacher job satisfaction and teacher performance, (2) Analyze the direct relationship between the role of the principal and teacher performance, (3) Analyze the relationship directly between teacher work motivation and teacher performance, (4) Analyzing the direct relationship between job satisfaction and teacher performance, (5) Analyzing the direct relationship between the role of the principal and motivation, (6) Analyzing the direct relationship between the role of the principal and job satisfaction, (7) Analyzing the indirect relationship between the role of the principal and teacher performance through teacher work motivation, (8) Analyzing the indirect relationship between the role of the principal and teacher performance through the variable job satisfaction. This research was conducted in Kandangan sub-district using quantitative approaches and descriptive methods. The research sample was 176 people. The instruments of data collection are questionnaires that have met the validity and reliability test requirements. Analysis of data to test hypotheses using path analysis with multiple regression methods. The results showed that: (1) Role of Principals, Work motivation and job satisfaction in Public Elementary Schools in Kandangan Subdistrict are very high classifications, while the performance of Public Elementary School teachers is Kandangan Subdistrict is in a high classification, (2) There is a relationship between the Principal's Role and the performance of State Elementary School teachers in Kandangan Subdistrict by 0,328. (3) There is a relationship between work motivation and the performance of state elementary school teachers in Kandangan subdistrict by 0,974. (4) There is a relationship between job satisfaction and the performance of State Elementary School teachers in Kandangan Subdistrict by 0,486, (5) There is a relationship between the role of the principal and the work motivation of Public Primary School teachers in Kandangan Subdistrict by 0,919, (6) the role of the school principal with the work satisfaction of state elementary school teachers in Kandangan subdistrict by 0.927, (7) There is an indirect relationship between the role of the principal and the teacher's performance through the work motivation of state elementary school teachers in Kandangan subdistrict by 0.895. (8) There is an indirect relationship between the Role of the Principal and the teacher's performance through the work satisfaction of State Primary School teachers in Kandangan Sub-district by 0.450.